Linking students' emotions to engagement and writing performance when learning Japanese letters with a pen-based tablet: An investigation based on individual pen pressure parameters. Issue 135 (March 2020) - Schrader, Claudia; Kalyuga, Slava
Highlights: Pen pressure parameters serve as indicators of enjoyment and frustration. Higher frustration leads to more pressure on a pen-based tablet. Higher enjoyment leads to less pressure on a pen-based tablet. The relation between pen pressure and writing performance is mediated by engagement. Abstract: In this paper, two studies were conducted to understand the link between students' emotions and their engagement and performance when learning to write Japanese letters with a learning technology involving a pen-based tablet. The incorporation of this haptic sensory modality in the form of a pen tablet is seen to have much potential for continuous emotional detection. In Study 1 (136 students, 84 females, Mage  = 23.55, SD  = 3.89), the learning effectiveness in terms of students' writing performance was assessed. We further examined the relationship between discrete learning-centered emotions such as enjoyment, frustration and boredom on the one hand, and pen pressure parameters on the other. The results demonstrated a significant gain in writing. Generalized estimating equation (GEE) models showed that minimum, maximum and average pen pressures all serve as indicators of enjoyment and frustration; on the other hand, for boredom, no significant relationships were found. Compared to enjoyment, the results demonstrate that, the higher a student's frustration when learning, the more pressure they apply to the pen when writing. In Study 2 (90 students, 60 females, Mage  = 22.94, SD  = 3.82), the findings from Study 1 were used to understand the practical implications of the results, investigating the relationship between emotion-based pen pressure, student engagement and writing performance over the course of the learning process. As in Study 1, the results, again, showed a significant gain in learning how to write Japanese letters. The partial least squares path model (PLS-PM) analyses revealed that higher pen pressure was a negative predictor of engagement, whereas higher engagement was a positive predictor of writing performance. Furthermore, the relationship between pen pressure and performance was mediated by engagement. Overall, the findings can contribute to our understanding of the interaction between students' emotions and different learning variables in an attempt to support the development of adaptive learning technologies.